Mechanism of Anisotropic Surface Self-Diffusivity at the Prismatic Ice-Vapor Interface - Rowe, P (Royal Society of Chemistry, 2015)
Predictive theoretical models for mesoscopic roughening of ice require improved understanding of attachment kinetics occurring at the ice-vapor interface. Here, we use classical molecular dynamics to explore the generality and mechanics of a transition from anisotropic to isotropic self-diffusivity on exposed prismatic surfaces. We find that self-diffusion parallel to the crystallographic a-axis is favored over the c-axis at sub-melt temperatures below about -35 °C, for three different representations of the water-water intermolecular potential. In the low-temperature anisotropic regime, diffusion results from interstitial admolecules encountering entropically distinct barriers to diffusion in the two in-plane directions. At higher temperatures, isotropic self-diffusion occurring deeper within the quasi-liquid layer becomes the dominant mechanism, owing to its larger energy of activation. © the Owner Societies 2015.